Comportamentos e valores relativos à informação em uma empresa do setor de transporte aéreo - Christine Conceicao Goncalves (2015)
This study describes and analyzes information behaviors and values within a Brazilian air transportation company. It was based on the Information Orientation (IO) model devised by Donald A. Marchand, William J. Kettinger and John D. Rollins (2001), as well as on theInformation Ecology and Use of Information models by Thomas Davenport (1998) and Joyce Kirk (2002), respectively. The IO model's key components are information technology practices, information management and information behaviors and values. In order todevelop this research, of both quantitative and qualitative applied nature, the analysis focused on the 'information behaviors and values' component. The data were collected by means of a questionnaire submitted to seventy eight managers of one of the company'sbranches; thirty two people filled and returned it. Six semi-structured interviews were also conducted to complement the study, which allowed for a deeper analysis of the results obtained through the questionnaire. To analyze the data, descriptive statistics was used to analyze the average values between variables, as well as Kendall nonparametric statistics to explore the association between the variables of the eight dimensions studied herein: proactive information use, transparency and formality as to the use of information, integrity, sharing, information use and control, and information culture. The data obtained from interviews were transcribed and analyzed by breaking the text down into analogicallygrouped categories so as to help understanding the discourses. Results show that managers recognize some information behaviors and values, although such results fall short of what the OI model's authors consider an information-directed company. Among the dimensions that provide a higher organizational performance, sharing, information use and controlprevailed.